Efficient One-Pot Synthesis of Novel Caffeic Acid Derivatives as Potential Antimalarials - Katarzyna Sidoryk; Silvia Parapini; Nicoletta Basilico; Magdalena Zaremba-Czogalla; Marek Kubiszewski; Marcin Cybulski; Jerzy Gubernator; Agnieszka Zagórska; Anna Jaromin (Journal of Parasitology Research)
New protocol for the preparation of the novel caffeic acid derivatives using the Wittig reaction has been applied to follow the principles of green chemistry. The compounds have been evaluated against chloroquine-sensitive and chloroquine-resistant P. falciparum strains. Their cytotoxicity to normal human dermal fibroblasts and their propensity to induce hemolysis have been also determined. Ethyl (2E)-3-(2,3,4-trihydroxyphenyl)-2-methylpropenoate has exhibited the highest antiplasmodial activity against P. falciparum strains without the cytotoxic and hemolytic effects. This derivative is significantly more potent than caffeic acid parent structure. The application of our one-step procedure has been shown to be rapid and efficient. It allows for an easy increase of input data to refine the structure-activity relationship model of caffeates as the antimalarials. The one-step approach meets the conditions of “atom economy” and eliminates hazardous materials. Water has been used as the effective medium for the Wittig reaction to avoid toxic organic solvents.